Is the Natural Instinct to Oviposit in Mated Female Oriental Fruit Fly, Bactrocera dorsalis More of a Brain-Independent Act? - Vyas, Meenal; Parepally, Saravan Kumar; Kamala Jayanthi, Pagadala Damodaram (Frontiers in Physiology, 2022)
What physiological and neuro-molecular changes control the female oviposition behavior post-mating in insects? The molecular changes that occur in a gravid female insect are difficult to dissect out considering the distinct behavioral patterns displayed by different insect groups. To understand the role of the brain center in Oriental fruit fly, Bactrocera dorsalis oviposition, egg-laying behavior was analyzed in γ-octalactone exposed, decapitated mated B. dorsalis females. Interestingly, the females displayed a possible urge to oviposit, which suggests a natural instinct to pass on the gene pool. Expression analysis of certain genes involved in oviposition behavior was also carried out in these insects to explore the molecular aspects of such behavior. This study tries to assess the involvement of brain center in egg-laying and also explore the role of certain neurotransmitter-related receptors in decapitated B. dorsalis oviposition behavior. Our results indicate that B. dorsalis oviposition behavior could potentially have a bypass route of neuronal control devoid of the brain. The study reported here establishes that decapitation in gravid females fails to abolish their ability to sense ovipositional cues and also to oviposit.